Kegiatan Pelakasanaan Pembelajaran PJOK di SD Negeri 060874 Medan - Suyono, Suyono; Ramadhani, Fitri; Siregar, Amandha Fhadillah; Azahra, Zelma (LPPPI Publishing, 2024)
Physical education is an integral part of the overall education system. This educational process utilizes physical activity to produce holistic changes in individual qualities both physically, mentally and emotionally. The motive for this research was to determine the implementation of physical education, sports and health learning activities at SD Negeri 060874 Medan City. This type of research is qualitative. Data collection techniques through observation, interviews and documentation. The results of the research are 1) The indicator for learning objectives is categorized as